1991
DOI: 10.1002/jlb.49.1.41
|View full text |Cite
|
Sign up to set email alerts
|

Cystatin C and Cathepsin B Production by Alveolar Macrophages From Smokers and Nonsmokers

Abstract: The capacity of alveolar macrophages (AM) obtained from smokers and nonsmokers to secrete cathepsin B and its inhibitor cystatin C was examined because of the concept that an imbalance in the production of proteolytic enzymes and/or their inhibitors could be responsible for the lung damage seen in smokers. Quantitation of immunoprecipitates on Western blots showed that the amount of total cystatin C secreted into the culture medium by AM of smokers was significantly greater than the amount secreted by cells ob… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
1

Year Published

1993
1993
2012
2012

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 21 publications
2
19
1
Order By: Relevance
“…The increased level of cystatin C observed in the BALF of smokers with subclinical emphysema described by TAKEYABU et al [14] and data on the elevated cystatin C levels produced by alveolar macrophages from smokers [34] are in good agreement with this hypothesis regardless of the underlying disease process. Cathepsin D deposits detected in the extracellular matrix in injured tissue do not preclude the possibility of extracellular cathepsin activities in the micromilieu of matrix proteins [35].…”
Section: Discussionsupporting
confidence: 65%
“…The increased level of cystatin C observed in the BALF of smokers with subclinical emphysema described by TAKEYABU et al [14] and data on the elevated cystatin C levels produced by alveolar macrophages from smokers [34] are in good agreement with this hypothesis regardless of the underlying disease process. Cathepsin D deposits detected in the extracellular matrix in injured tissue do not preclude the possibility of extracellular cathepsin activities in the micromilieu of matrix proteins [35].…”
Section: Discussionsupporting
confidence: 65%
“…There have been two conflicting reports on the level of cystatin C in the culture medium of alveolar macrophages from smokers and nonsmokers. CHAPMAN et al [13] demonstrated that the level was lower in smokers than in nonsmokers, whereas WARFEL et al [30] reported the opposite findings. However, there have been no reports on the level of cystatin C in BAL fluid from subjects with emphysema.…”
Section: Discussionmentioning
confidence: 97%
“…It is a 14-kDa protein (120 amino acids) and is secreted by different cell types in vitro (27). Several proteinase inhibitors, such as thrombin inhibitors, calpain inhibitors, or cysteine protease inhibitors, have been suggested to be part of a regulatory system associated with neuronal differentiation.…”
Section: Discussionmentioning
confidence: 99%